The impact of employee empowerment on employee satisfaction and service quality: empirical evidence from financial enterprizes in Bangladesh - Ukil, Minhajul Islam (Business: Theory and Practice, 2016)
Organizations face immense challenges in improving their performance and productivity in the present changing and competitive business world. Experts view employee empowerment as an effective tool that fosters organizational performance, employee satisfaction and service quality. The present study intends to identify the influence of employee empowerment on employee satisfaction and service quality, and the impact of employee satisfaction on service quality. Fourteen dimensions and 52 item statements of employee empowerment, service quality and employee satisfaction have been adopted from previous studies to undertake this study. Data have been gathered following a quantitative survey conducted among a diverse group of employees (N = 240) working in 20 different financial institutions including private banks, leasing and insurance companies in Bangladesh. Several statistical techniques consisting of descriptive analysis, Pearson correlations and regression analysis have been applied using SPSS software to analyze collected data. The results of the statistical analysis reveal that employee satisfaction and service quality significantly depend on employee empowerment, and satisfied employees provide better quality service. The findings of this research have explicit implications for both the employees and the organizations. This study suggests that by empowering employees, an organization can increase the level of employee satisfaction that in consequence upturns service quality.